Pelvic Inflammatory Disease and Involuntary Infertility: Prospective Pilot Observations - David Soper; Roberta B. Ness (Hindawi Limited, 1995)
Objective: We prospectively evaluated the rate of adverse reproductive outcomes following pelvic inflammatory disease (PID) in a small cohort of American women.